Science Process Skills-Based Integrated Instructional Materials to Improve Student Competence Physics Education Prepares Learning Plans on Teaching Skills Lectures - Desnita Desnita; Dwi Susanti (Jurnal Penelitian & Pengembangan Pendidikan Fisika, 2017)
Abstract Integrated learning materials was developed, consisting of syllabus revision eddition, One Semester Plan, module, student work sheet, and student performance appraisal sheet for Physics Teaching Skills course. The subject matter have been developed are the skills to ask and skill explain. This research product has been validated by colleagues in Physics Education program of Faculty of Mathematics and Natural Sciences of Universitas Negeri Jakarta. Friends of colleagues agreed to use this research product in lectures on teaching skills. The student's response to teaching materials was measured using a questionnaire consisting of 14 number of statement, the average score of the students' assessment of 88.86 teaching materials means the student's response to the excellent teaching materials. This teaching material trains the science process skills of physics education students and also provides experience to the students to independently assess performance. The results of the product test on the students gave excellent results, where the average score of student performance for questioning skills was very good 85.3; While the average student performance score for the skills explained 87.9 it’s same category. The results of the experiment proved that the integrated teaching materials development outcomes are worthy of use in the course of Physic Teaching Skills. Keywords: integration learning materials, science process skills, physic teaching skills. Abstrak Telah dikembangkan bahan ajar terintegrasi, yang terdiri dari revisi silabus, Rencana Perkuliahan Satu Semester (RPS), modul, lembar kegiatan mahasiswa, dan lembar penilaian kinerja mahasiswa untuk mata kuliah Keterampilan Mengajar Fisika. Bahan ajar terintegrasi yang telah dikembangkan, untuk keterampilan bertanya dan keterampilan menjelaskan. Produk penelitian ini sudah divalidasi oleh teman sejawat pada program Studi Pendidikan Fisika FMIPA Universitas Negeri Jakarta. Teman sejawat sepakat untuk menggunakan produk penelitian ini dalam perkuliahan Keterampilan Mengajar. Respon mahasiswa terhadap bahan ajar diukur menggunakan angket yang terdiri dari 14 butir, rata-rata skor penilaian mahasiswa terhadap bahan ajar 88,86 artinya respon mahasiswa terhadap bahan ajar sangat baik. Bahan ajar ini melatih keterampilan proses sains mahasiswa pendidikan fisika dan juga memberikan pengalaman kepada mahasiswa untuk menilai kinerja secara mandiri Hasil ujicoba produk terhadap mahasiswa memberikan hasil sangat baik, dengan nilai rata-rata kinerja mahasiswa untuk keterampilan bertanya 85,3 sangat baik; sedangkan rata-rata nilai kinerja mahasiswa untuk keterampilan menjelaskan 87,9 juga sangat baik. Hasil ujicoba membuktikan bahwa bahan ajar terintegrasi hasil pengembangan layak digunakan pada mata kuliah Keterampilan Mengajar Fisika. Kata-kata kunci: bahan ajar terintegrasi, keterampilan proses sains, keterampilan mengajar fisika.